Exosomes in Pathogen Infections: A Bridge to Deliver Molecules and Link Functions - Zhang, Wenchao; Jiang, Xiaofeng; Bao, Jinghui; Wang, Yi; Liu, Huixing; Tang, Lijun (Frontiers in Immunology, 2018)
Exosomes are extracellular vesicles derived from cell endocytosis which act as transmitters between cells. They are composed of proteins, lipids and RNAs through which they participate in cellular crosstalk. Consequently, they play an important role in health and disease. Our view is that exosomes exert a bidirectional regulatory effect on pathogen infections by delivering their content. Firstly, exosomes containing proteins and RNAs derived from pathogens can promote infections in three ways: (1) mediating further infection by transmitting pathogen-related molecules; (2) participating in the immune escape of pathogens; (3) inhibiting immune responses by favoring immune cell apoptosis. Secondly, exosomes play anti-infection roles through: (1) inhibiting pathogen proliferation and infection directly; (2) inducing immune responses such as those related to the function of monocyte-macrophages, NK cells, T-cells and B-cells. We believe that exosomes act as “bridges” during pathogen infections through the mechanisms mentioned above. The purpose of this review is to describe present findings regarding exosomes and pathogen infections, and highlight their enormous potential in clinical diagnosis and treatment. We discuss two opposite aspects: infection and anti-infection, and we hypothesize a balance between them. At the same time, we elaborate on the role of exosomes in immune regulation.